Perbedaan Tingkat Pemahaman Konsep Sains Mahasiswa Calon Guru SD Ditinjau Dari Background Jurusan Sekolah Asal - Hasnawati Hasnawati; Muhammad Syazali; Arif Widodo (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Understanding of science concepts is part of the professional competencies that must be mastered by prospective elementary school teachers. This study aims to compare whether there are differences in the understanding of science concepts for elementary school teacher candidates who majored in science and non-science at senior high school. It is hoped that the research results can be used as evaluation material for lecturers in designing learning in science concept courses in tertiary institutions. This research uses a quantitative survey type method. The subjects in this study were elementary school teacher candidates. The number of samples in this study were 110 students with details of 68 coming from science majors and 42 coming from non-science majors. Data collection uses a scientific concept understanding test. Data were analyzed using the Mann-Whitney test. The results showed that the understanding of science concepts for students from science majors scored a mean rank of 62.67, while the mean rank of non-science majors was 43.89. Based on the results of the Mann-Whitney test, a value was obtained. Sig. (2-tailed), namely 0.003 <0.05, which means that there is a difference in the ability to understand science concepts between groups of students who have backgrounds in science and non-science majors. Based on the results of this study, it is recommended that lecturers conduct matriculation or introduce science concepts before learning and adapt learning to students with non-science majors backgrounds so that they have an understanding of science concepts that are on par with students with science majors backgrounds.